Collective Inclusioning - Michal Lysek (Grounded Theory Review: An International Journal, 2016)
This paper is a grounded theory study of how leaders (e.g., entrepreneurs, managers, etc.) engage people in challenging undertakings (e.g., innovation) that require everyone’s commitment to such a degree that they would have to go beyond what could be reasonably expected in order to succeed. Company leaders sometimes wonder why their employees no longer show the same responsibility towards their work, and why they are more concerned with internal politics than solving customer problems. It is because company leaders no longer apply collective inclusioning to the same extent as they did in the past. Collective inclusioning can be applied in four ways by convincing, afinitizing, goal congruencing, and engaging. It can lead to fostering strong units of people for taking on challenging undertakings. Collective inclusioning is a complementing theory to other strategic management and leading theories. It offers a new perspective on how to implement a bottom-up approach to innovation.